A rare case of gastric pneumatosis in a seven-month-old infant – case report - Socha, Anna; Socha-Banasiak, Anna; Pacześ, Krzysztof; Makosiej, Ryszard; Czkwianianc, Elżbieta (Pediatria Polska - Polish Journal of Paediatrics, 2020)
Pneumatosis is a rare condition characterised by the presence of gas collections within the wall of the alimentary tract occurring both in paediatric and adult patients. In this manuscript, we present a seven-month-old boy admitted to our department due to episodes of emesis and prolonged diarrhoea. Initial X-ray of the abdomen revealed a significantly dilated stomach with gas collections within its wall. The boy was diagnosed with stomach wall pneumatosis resulting from paralytic ileus caused by prolonged gastric infection. After immediate nasogastric decompression, implementation of broad-spectrum antibiotics, and temporary total parenteral nutrition complete resolution of gastric pneumatosis and clinical improvement were achieved.